'View From A Bridge': A New Perspective on Eukaryotic rRNA Base Modification. Issue 10 (October 2015) - Sharma, Sunny; Lafontaine, Denis L.J.
<x xml:space="preserve">Abstract</x> Eukaryotic rRNA are modified frequently, although the diversity of modifications is low: in yeast rRNA, there are only 12 different types out of a possible natural repertoire exceeding 112. All nine rRNA base methyltransferases (MTases) and one acetyltransferase have recently been identified in budding yeast, and several instances of crosstalk between rRNA, tRNA, and mRNA modifications are emerging. Although the machinery has largely been identified, the functions of most rRNA modifications remain to be established. Remarkably, a eukaryote-specific bridge, comprising a single ribosomal protein (RP) from the large subunit (LSU), contacts four rRNA base modifications across the ribosomal subunit interface, potentially probing for their presence. We hypothesize in this article that long-range allosteric communication involving rRNA modifications is taking place between the two subunits during translation or, perhaps, the late stages of ribosome assembly.